A abordagem do modelo atômico de Bohr através de atividades experimentais e de modelagem - Silva, Giovanna Stefanello (2013)
Knowing and understanding the Chemistry concepts is directly related to the capability of moving between the three levels of representation which concern Chemistry. Each one of these levels involve the developing of different abilities, as the capability of abstraction. There are several Chemistry concepts which depend on this articulation between the macroscopic, microscopic and symbolic levels, for example, the study of the matter structure. Though, it is noticed that a large part of the students show difficulties in comprehending the transition between the levels of representation and therefore identifying the relation between the chemical concepts and their everyday lives, this is why it is important to know the concepts of the students. With the purpose of helping the students in the construction, visualization and application of the knowledge which involve the study of the atom, especially the Bohr atomic model, with facts of their daily lives, in this study we elaborated and developed different experimental and modeling activities. Moreover, we evaluated the didactic objective of the visual resources present in the five textbooks approved by the PNLD-2012, in relation to the atomic structure. This analysis was done duo to the importance of this material in class and its use as research source in some activities developed in this research, as the images present in the textbooks may help the students in the relation between the theory and the practice during the process of imagining some chemical phenomenon. In a general way, we observed that there is diversity in the way the visual resources are used in the textbooks concerning the Bohr atomic model. This study was taken with thirty seven subjects in a class of freshman students in the city of Júlio de Castilhos, RS. The data taken in seven interventions was analyzed and categorized according to the methodology of the discursive text analyses. After the analyses of the data, the results showed that the different developed interventions, either through experimental or modeling activities, collaborated to the students to correlate the chemical concepts acquired in the classroom with several phenomena of their routine. Furthermore, it helped them to formulate their own relation between the macroscopic and the microscopic by their own observation, discussion, and idea interpretation using the Chemistry codes and symbols. Thus it can be said that, after the interventions, students were able to move between the three levels of representation of matter. These implications show that the teaching of Chemistry needs to provide students with differentiated classes in the attempt that they are able to identify and relate Chemistry as an integral part of their lives.